Spatio-temporal variations and influencing factors of polycyclic aromatic hydrocarbons in atmospheric bulk deposition along a plain-mountain transect in western China. (August 2016) - Xing, Xinli; Zhang, Yuan; Yang, Dan; Zhang, Jiaquan; Chen, Wei; Wu, Chenxi; Liu, Hongxia; Qi, Shihua
Abstract: Ten atmospheric bulk deposition (the sum of wet and dry deposition) samplers for polycyclic aromatic hydrocarbons (PAHs) were deployed at a plain-mountain transect (namely PMT transect, from Daying to Qingping) in Chengdu Plain, West China from June 2007 to June 2008 in four consecutive seasons (about every three months). The bulk deposition fluxes of ∑15 -PAHs ranged from 169.19 μg m −2  yr −1 to 978.58 μg m −2  yr −1 with geometric mean of 354.22 μg m −2  yr −1 . The most prevalent PAHs were 4-ring (39.65%) and 3-ring (35.56%) PAHs. The flux values were comparable to those in rural areas. Higher fluxes of total PAHs were observed in the middle of PMT transect (SL, YX and JY, which were more urbanized than other sites). The seasonal deposition fluxes in the sampling profile indicated seasonality of the contaminant source was an important factor in controlling deposition fluxes. PAHs bulk deposition was negatively correlated with meteorological parameters (temperature, wind speed, humidity, and precipitation). No significant correlations between soil concentrations and atmospheric deposition were found along this transect. PAHs in soil samples had combined sources of coal, wood and petroleum combustion, while a simple source of coal, wood and grass combustion for bulk deposition. There were significant positive correlation relationship (p < 0.05) between annual atmospheric bulk deposition and local PAHs emission, with biomass burning as the major contribution to the total emission of PAHs. This transect acts as an important PAHs source rather than being a sink according to the ratio of deposition/emission. Mountain cold trap effect existed in this transect where the altitude was higher than 1000 m. Long-range transport had an impact on the bulk deposition in summer. And this transect was a source to Tibetan only in summer. The forward trajectory analysis showed most air masses did not undergo long-range transport due to the blocking effect of surrounding mountains. Only a few air masses (<10%) arrived at the eastern and northern region of China or farther regions via long-range transport. Highlights: Spatio-temporal variations of PAHs in atmospheric deposition were observed. PAHs deposition was negatively correlated to some meteorological parameters. Atmospheric PAHs deposition was closely related to local emission. This transect played an important role of source rather than sink. Most air mass did not undergo long-range transport due to the presence of mountains.